A comparison of insulin detemir and neutral protamine Hagedorn (isophane) insulin in the treatment of diabetes: a systematic review. Issue 11 (1st May 2013) - Frier, B. M.; Russell‐Jones, D.; Heise, T.
<x xml:space="preserve">Abstract</x> The aim of this review is to summarize the clinical efficacy, tolerability and safety data of insulin detemir, and compare its use with that of neutral protamine Hagedorn (NPH) insulin in randomized controlled trials in people with type 1 or type 2 diabetes. A literature search was conducted with PubMed using predefined search terms. Studies were included if they met the following criteria: randomized, controlled trial, comparison of insulin detemir with NPH insulin, non‐hospitalized adults aged ≥18 years with either type 1 or type 2 diabetes, and study duration of ≥12 weeks. The following types of studies were excluded: non‐randomized controlled trials, studies of mixed cohorts of patients with type 1 or type 2 diabetes that did not report results separately, pharmacokinetic/pharmacodynamic studies, reviews, pooled or meta‐analyses or health‐economic analyses. Fourteen publications met the inclusion criteria. Nine studies in people with type 1 diabetes and three studies in people with type 2 diabetes, using insulin detemir in a basal–bolus regimen were included. Two studies were in people with type 2 diabetes using insulin detemir with oral antidiabetes medicines. In 14 studies of people with type 1 or type 2 diabetes, insulin detemir treatment provided similar or better glycaemic control, lower within‐subject variability, similar or lower frequency of hypoglycaemia and less weight gain when compared with NPH insulin.